PELUANG HEMAT ENERGI LISTRIK PADA GARDU FISIP KAMPUS UNIVERSITAS TADULAKO - Siregar, Restu Ary Winata; E, Darmawan; Mukhlis, Baso; Rahman, Yuli Asmi (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2016)
The use of electrical energy in University is an absolute and unavoidable. Based on data obtained, every year Tadulako University experienced a high increase in electrical energy consumption. The electricity bills of Tadulako University based on data 8 months from January to August 2015 reached Rp.2.567.411.878 that is in average of payment per month of Tadulako University is Rp.322.051.485.At the substation of FISIP electricity usage in January through August 2015 was highest in June reaching 61.750 kWh to the cost of electricity bill as big as Rp.55.575.000. Electric energy audit begins with the historical data collection of electricity biil in the last three years such as : the substation of FISIP on January to August, the data load of electrical equipment, and the spacious rooms supplied. The intensity of energy consumption and the energy-saving opportunities were counted from each supplied rooms of substation FISIP. The result of the calculation of the intensity of energy consumption in detail can be seen throught 160 total rooms if the energy-saving opportunity of 49 rooms is implemented. Therefore, Tadulako University can save the cost of electricity by Rp.30.140.900,73 per month. Keywords : Electrical Energy Audit, Energy Consumption Intensity, Energy Saving Opportunities, Efficiency, Substation FISIP, Tadulako University